Blogs and the Art of Dying: Blogging With, and About, Severe Cancer in Late Modern Swedish Society. (September 2019) - Andersson, Yvonne
In recent years, the common and mundane dying has begun to take place in the public space of the Internet. Among the blogs about food, fashion, travel, and other joyful aspects of life, blogs about severe disease and dying have appeared. The aim of this article is to describe some characteristic features of a sample of cancer blogs and to discuss them in the light of Zygmunt Bauman's theory of the rationalization of death in modernity and theories about networked media, especially the theories about "affective labor" and "ambient intimacy" by McCosker, Darcy, and Pfister. It will then be argued that an affective communication is performed in and through these cancer blogs, where not only language but also the deficiencies of language—and what is called shared ineffability —might be valuable and meaningful (although not unproblematic) as part of a late modern approach to death, and in the practicing of the art of dying.